A Feasibility Study of the Addition of STEPPS in Outpatients With Bipolar Disorder and Comorbid Borderline Personality Features: Promises and Pitfalls - Riemann, Georg; Chrispijn, Melissa; Weisscher, Nadine; Regeer, Eline; Kupka, Ralph W. (Frontiers in Psychiatry, 2021)
Background: Pharmacotherapy is a cornerstone in bipolar disorder (BD) treatment whereas borderline personality disorder (BPD) is treated primarily with psychotherapy. Given the overlap in symptomatology, patients with BD may benefit from psychotherapy designed for BPD. Aims: This paper reports on the presence of borderline personality features (BPF) in BD patients, and the findings of a non-controlled open feasibility study of STEPPS training in patients with BD and BPF. Methods: Outpatients with BD were screened for BPD, and if positive interviewed with SCID-II. Patients with at least three BPF, always including impulsivity and anger burst, were included in the intervention study. Severity of BD and BPD and quality of life were assessed. Descriptive statistics were performed. Results: Diagnostic study: 49.5% of 111 patients with BD also screened positive on BPD according to PDQ-4+, and 52.3% of these had BPD according to SCID-II. Intervention study: nine patients completed STEPPS and showed improvement on all outcome variables post treatment, but no longer at six-month follow up. Conclusion: Features of BPD were highly prevalent in patients with BD. Still, recruiting patients for a psychological treatment originally designed for BPD proved to be difficult. Feedback of participants suggests that the terminology about ‘borderline’ in the study had an aversive effect, which may have caused drop-out before the treatment stage. Therefore, STEPPS should be adapted for BD to be an acceptable treatment option.